BIOREMEDIATION OF TOTAL PETROLEUM HYDROCARBON POLLUTED SOIL FROM AN ABADONED ILLEGAL CRUDE OIL REFINING SITE USING ORGANIC AMENDMENTS - Pallavi C.N (Global Journal of Plant and Soil Sciences, 2023)
This study was carried out to evaluate the bioremediation of total petroleum hydrocarbon (TPH) polluted soil from an abandoned illegal crude oil refining site using organic amendments: fish pond effluent (FPE), spent mushroom substrate (SMS) and compost soil (CS) from an old waste dump site. Baseline studies on the polluted soil samples were carried out. The treatment options were four experimental setups including control in clay pots. The setups were left to stand for 28days and monitored every 7 days using stan- dard microbiological techniques and gas chromatography. The baseline TPH result was 25,350.2 ± 0.21 mg/kg. This was above the DPR intervention limit, which means remedial action is required. Total heterotrophic bacterial (THB) counts ranged from: 1.3 ± 0.05 x 105 to 2.3 ± 0.04 x 106 Cfu/g, Total fungal counts ranged from 9.0 ± 0.01 x 104 to 7.0 ± 0.01 x 105 Cfu/g, Hydrocarbon utilizing bacte- rial (HUB) counts ranged from 1.0 ± 0.04 x 105 to 1.32 ± 0.04 x 106 Cfu/g, Hydrocarbon utilizing fungal (HUF) counts ranged from: 7.0 ± 0.02 x 104 to 5.1 ± 0.18 x 105 Cfu/g all across the setups. FPE gave a half-life of 9.6 days with TPH degradation of 88.27%, SMS had TPH degradation of 82.12% with a half-life of 12.2 days, CS gave TPH degradation of 75.53% and a half-life of 14.81 days and the control had the least TPH degradation of 6.0% and a longer half-life of 315.1 days. The following bacteria and fungi were isolated and identified: Psuedomonas sp, Bacillus sp, Micrococcus sp, Chromobacterium sp, Alcaligenes sp, Arthrobacter sp, Fusarium sp, Rhizopus sp, Mucor sp, Aspergillus fumigates, Penicillium sp, Cryptococcus sp, Aspergillus lentulus, Rhodotolola sp. These results show that, the addition of these amendments and the natural resident flora enhanced the TPH degradation, with FPE giving the highest bioremedia- tion percent. Hence, FPE may be recommended to be applied in the bioremediation of petroleum polluted soil.